Copolymer based on lauryl methacrylate and poly(ethylene glycol) methyl ether methacrylate as amphiphilic macrosurfactant: Synthesis, characterization and their application as dispersing agent for carbon nanotubes. (February 2017) - Iborra, Agustín; Díaz, Gisela; López, Daniel; Giussi, Juan Martín; Azzaroni, Omar
Graphical abstract: Highlights: Amphiphilic copolymer based on lauryl and Poly(ethylene glycol) methyl ether methacrylate. Different sizes of the formed micelles depending on solvent polarity. Incorporation of small amounts of organic solvent in water, and vice versa. Good dispersion of carbon nanotubes in water. Abstract: The use of amphiphilic macrosurfactants as emulsifying agents has shown to have higher efficiency than that of low molecular weight surfactants. Compared to traditional surfactants, polymeric surfactants have lower critical micelle concentrations and lower diffusion coefficients. In this paper, we present a well defined copolymer based on lauryl methacrylate and poly(ethylene glycol) methyl ether methacrylate, prepared by solution radical copolymerization. The product was characterized by NMR and FTIR spectroscopies and the weight-average molecular weight and polydispersity index were analyzed by SEC. The thermal transitions and decomposition temperatures of the copolymers were determined by DSC and TGA, respectively. Due to the hydrophobic and hydrophilic nature of the monomer units, emulsification studies were performed. DLS experiments showed different sizes of the formed micelles depending on solvent polarity due to polymer-polymer or polymer-solvent interactions. Rheological characterization was undertaken to study the viscoelastic properties of the dispersed systems. Finally, two types of experiments to evaluate the polymer abilities as surfactant have been carried out. Firstly, the amphiphilic characteristics of this material allowed the incorporation of small amounts of an organic solvent in water forming only one phase, as well as the incorporation of small amounts of water in the organic solvent forming an emulsified phase. Then, the amphiphilic properties of this macrosurfactant have been fully exploited in order to form highly stable dispersions of carbon nanotubes in water.